Finite element modeling of the eyeglass-related traumatic ocular injuries due to high explosive detonation. (November 2020) - Razaghi, Reza; Biglari, Hasan; Karimi, Alireza
Highlights: Eyeglass-related traumatic ocular injuries due to high explosive detonation were simulated. Patient-specific skull and eye models were employed for our FE simulation. Injuries due to PBW was found to be more severe than that of the broken glass shards. The sclera experienced the highest stress, which might be the leading site for globe rupture. Abstract: Traumatic ocular injury due to glass shards is a challenging issue that might occur due to automobile crashes, airbag expansions, military operations, sports, etc. Eyeglass breakage due to a high explosive detonation, shoot a group of randomly sized shards into the eye at a dramatically high speed along with a primary blast wave (PBW) propagation which might invoke extensive scarring and damage to the internal ocular tissues following by permanent visual impairment. Understanding the mechanisms of this injury and its following complications in each component of the eye might not be achievable experimentally unless using numerical simulations, i.e., finite element method (FEM). Although our group performed two separate studies to investigate the ocular injury because of glass shards and high explosive detonation, it would be interesting to understand how the combination of these two together damage the components of the eye. Therefore, this study was aimed to compute the stresses and deformations in the eye components, including the cornea, aqueous body, iris, ciliary body, lens, vitreous body, retina, sclera, optic nerve, orbital muscle, and orbital fat (intraconal and extraconal), attributed to glass shards breaking down because of PBW induced by trinitrotoluene (TNT) explosion. A three-dimensional (3D) FE model of the eye globe was established using CT/MRI data and subjected to glass shards at a high speed resulted from a TNT explosion. The injury to the components of the eye and the skull were calculated right after the blast wave and right after the glass shards reach to the eye/skull to reveal the role of each factor separately. The highest amount of stresses/injuries occurred in the sclera, which might trigger eye globe rupture. These findings may contribute in understanding of the mechanisms of ocular injury aiding in the management of the eyeglass-related traumatic injuries due to explosion, car accident injuries and or combat injuries.